Excessive fuel availability amplifies the FTO-mediated obesity risk: results from the TUEF and Whitehall II studies. Issue 1 (December 2017) - Wagner, Róbert; Tabák, Ádám; Fehlert, Ellen; Fritsche, Louise; Jaghutriz, Benjamin; Bánhegyi, Róbert; Schmid, Sebastian; Staiger, Harald; Machicao, Fausto; Peter, Andreas; Häring, Hans-Ulrich; Fritsche, Andreas; et al.
Abstract Variation inFTO is the most important common genetic determinant of body weight. Altered energy metabolism could underlie this association. We hypothesized that higher circulating glucose or triglycerides can amplify theFTO impact on BMI. In 2671 subjects of the TUEF study, we investigated the interaction effect of fasting glucose and triglyceride levels with rs9939609 inFTO on BMI. We analysed the same interaction effect by longitudinally utilizing mixed effect models in the prospective Whitehall II study. In TUEF, we detected an interaction effect between fasting glucose and fasting triglycerides with rs9939609 on BMI (p = 0.0005 and p = 5 × 10−7, respectively). The effect size of one risk allele was 1.4 ± 0.3 vs. 2.2 ± 0.44 kg/m² in persons with fasting glucose levels below and above the median, respectively. Fasting triglycerides above the median increased the per-allele effect from 1.4 ± 0.3 to 1.7 ± 0.4 kg/m2 . In the Whitehall II study, body weight increased by 2.96 ± 6.5 kg during a follow-up of 13.5 ± 4.6 yrs. Baseline fasting glucose and rs9939609 interacted on weight change (p = 0.009). Higher fasting glucose levels may amplify obesity-risk inFTO carriers and lead to an exaggerated weight gain over time. Since weight gain perpetuates metabolic alterations, this interplay may trigger a vicious circle that leads to obesity and diabetes.